Preferential Begging Responses of Shiny Cowbirds to the Conspecific Chatter Call - Crudele, Ignacio; Reboreda, Juan C.; Fiorini, Vanina D. (Frontiers in Ecology and Evolution, 2022)
Avian brood parasites lay their eggs into the nests of other species, which incubate them and raise the chicks until their independence. Despite living their early weeks of life surrounded by heterospecifics, young brood parasites have the ability to recognize and associate to conspecifics after independence. It has been proposed that the initial conspecific recognition develops when a young parasite encounters a unique species-specific signal that triggers the learning of other aspects of the signal’s producer. For cowbirds (Molothrus spp.), this species-specific signal is hypothesized to be the chatter-call. Young birds also could express auditory biases, which in some cases lead to discrimination in favor of conspecific songs. Therefore, the perceptual selectivity for chatters might be also present in nestlings. Our aim was to assess if shiny cowbird (M. bonariensis) nestlings present a preferential begging response to conspecific chatter-calls. We evaluated if they respond more to the parasitic vocalization than host chicks and if they respond more to the chatter than to heterospecific non-host calls. We tested shiny cowbird chicks reared by chalk-browed mockingbirds (Mimus saturninus) or house wrens (Troglodytes aedon) and host chicks, as control species. We randomly presented to six-days-old chicks the following playback treatments: 1) conspecific chatter-calls, 2) host calls, used as positive controls, and 3) non host calls, used as negative control. We measured if chicks begged during the playback treatments and the begging intensity. When responding to the playback of chatter-calls, shiny cowbird chicks begged at a higher frequency and more intensively than host chicks. Shiny cowbird chicks reared by mockingbirds begged more intensively to playbacks of conspecific chatter-calls than to host calls while those reared by wrens begged with a similar intensity to playbacks of conspecific chatter and host calls. On the contrary, wren nestlings begged more intensively to playbacks of wren call than to chatter-calls. Mockingbird nestlings did not beg during any treatment. None of the three species begged during the playback of non-host calls. Our results show that the chatter-call produced a preferential begging response in cowbird nestlings which may be the beginning of a process of conspecific recognition.